Theoretical aspects of human capital formation in the interaction between the economic and education sectors - Mietule, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In the 21st century, together with the development of society and economics, including technology, the importance of human capital as a production resource is not decreasing, on the contrary – it is growing. Today’s situation in the EU countries (demographic and ethnic problems) makes us consider the leading role of population as human capital in the development of economics as well as evaluate human capital formation conditions. The aim of the research is to explore theoretical aspects of human capital concerning the mutual interaction of the fields of economics and education. In the economic theory, there have been hot debates regarding human capital, its formation necessity, costs and benefits from the state and individual’s point of view. From the author’s point of view, the role of employer being a moving force in forming human capital is underestimated. It is crucial to involve employers in the formation of the human capital, making a dialogue in relation to the implementation of professional and higher education programmes.